Automating efficiency-targeted approximations in modelling and simulation tools: dynamic decoupling and mixed-mode integration. (October 2014) - Papadopoulos, Alessandro Vittorio; Leva, Alberto
Modelling and simulation nowadays permeate virtually any engineering activity, requiring tools capable of managing complex models efficiently. Nonetheless, whereas modern modelling languages and tools allow such models to be constructed even on lightweight platforms (e.g. a laptop), the same is not true when it comes to numerically integrating those models. For the latter purpose, modellers usually pursue efficiency by resorting to approximation and reduction techniques. However, such techniques are unnatural to include in modelling and simulation tools. This is particularly true with object-oriented ones, which on the other hand are the most interesting for dealing with complexity from the model construction viewpoint. This paper presents a novel approximation technique that can be easily included in modelling and simulation tools, and relates the proposal to literature alternatives so as to provide evidence of its peculiarities. An extended manipulation toolchain is also proposed, allowing for the introduction of other (classical) efficiency-targeted approximation techniques, within a unified framework. Some application examples illustrate the achieved advantages and motivate the major design choices from an operational viewpoint.